The Diagnostic Performance of Non-Rim Arterial Phase Hyperenhancement in LI-RADS 5 Categorization for Hepatocellular Carcinoma: A Histopathological Correlation (Bangladesh Journal of Radiology and Imaging, 2026)
Background: Hepatocellular carcinoma (HCC) is the most common primary liver malignancy and a leading cause of cancer-related mortality worldwide. Early and accurate diagnosis is essential for timely treatment and improved prognosis. Triphasic MRI, in combination with the Liver Imaging Reporting and Data System (LI-RADS), allows non-invasive evaluation of liver lesions, with non-rim arterial phase hyperenhancement (APHE) as a key feature for LR-5 categorization.Objective: To assess the diagnostic performance of non-rim APHE in LI- RADS 5 categorization for HCC, using histopathology as the reference standard.Methods: A cross-sectional study included 30 patients with suspected hepatic lesions who underwent triphasic MRI. Lesions were categorized according to LI-RADS from April 2024 to September 2025. criteria, and imaging findings were correlated with histopathology. Diagnostic parameters including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), likelihood ratios, and accuracy were calculated using SPSS. Statistical significance was determined with Fisher’s exact test (p < 0.05).Results: Of 30 lesions, 18 (60%) were confirmed as HCC. Sixteen lesions were categorized as LR-5, of which 15 were true positives and 1 false positive. Sensitivity and specificity of LR-5 for HCC detection were 83.3% and 91.7%, respectively. PPV was 93.8%, NPV 78.6%, and overall accuracy 86.7%. Non-rim APHE was observed in 29 lesions (96.7%), while capsular appearance and washout features were present in 43.3% and 46.7% of lesions, respectively.Conclusion: Non-rim APHE is a pivotal imaging feature for LI-RADS 5 categorization. Triphasic MRI interpreted using LI-RADS provides high diagnostic accuracy and can guide non-invasive management of HCC, reducing the need for biopsy in most cases.